Dorsal premotor cortex is involved in switching motor plans - Pastor-Bernier, Alex; Tremblay, Elsa; Cisek, Paul (Frontiers in Neuroengineering, 2012)
Previous studies have shown that neural activity in primate dorsal premotor cortex (PMd) can simultaneously represent multiple potential movement plans, and that activity related to these movement options is modulated by their relative subjective desirability. These findings support the hypothesis that decisions about actions are made through a competition within the same circuits that guide the actions themselves. This hypothesis further predicts that the same cells reflecting initial decisions will continue to update their activities as an animal changes its mind, for example, when a selected movement option suddenly becomes unavailable. We tested this prediction by recording neural activity in the PMd of a monkey performing an instructed-delay reach selection task. In the task, two targets were simultaneously presented and their border styles indicated whether each would be worth 1, 2 or 3 juice drops. In a random subset of trials (FREE), the monkey was allowed a choice while in the remaining trials (FORCED) one of the targets disappeared at the time of the GO signal. In FORCED-LOW trials the monkey was forced to move to the less valuable target and started moving either toward the new target (Direct) or toward the target that vanished and then curved to reach the remaining one (Curved). Prior to the GO signal, PMd activity clearly reflected the monkey’s subjective preference, predicting his choices in FREE trials even with equally valued options. In FORCED-LOW trials, PMd activity reflected the switch of the monkey’s plan as early as 100ms after the GO signal, well before movement onset. This confirms that the activity is not related to feedback from the movement itself, but that PMd continues to participate in action selection even when the animal changes its mind on-line. These findings were reproduced by a computational model suggesting that switches between action plans can be explained by the same competition process responsible for initial decisions.